2010
DOI: 10.1186/1471-244x-10-60
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and hierarchical models of depression using the Beck Depression Inventory-II in an Arab college student sample

Abstract: BackgroundAn understanding of depressive symptomatology from the perspective of confirmatory factor analysis (CFA) could facilitate valid and interpretable comparisons across cultures. The objectives of the study were: (i) using the responses of a sample of Arab college students to the Beck Depression Inventory (BDI-II) in CFA, to compare the "goodness of fit" indices of the original dimensional three-and two-factor first-order models, and their modifications, with the corresponding hierarchical models (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 64 publications
(131 reference statements)
5
32
1
Order By: Relevance
“…21,58,67,73,87,101,105 Although still scant, the bifactor model (G) was able to identify a non-hierarchical general depression in addition to the traditional two-dimensional structure. 18,34,64,81,84,96,121 These investigations shared the view that much of the variance of the BDI-II items can be accounted for by a hierarchical higher order or a parallel dimension of depression, where much of the common variance can be explained by a general construct. Practitioners should be careful when interpreting subscale scores, which might be greatly related to the heterogeneous characteristics of depressive conditions.…”
Section: Content and Construct Validitymentioning
confidence: 67%
“…21,58,67,73,87,101,105 Although still scant, the bifactor model (G) was able to identify a non-hierarchical general depression in addition to the traditional two-dimensional structure. 18,34,64,81,84,96,121 These investigations shared the view that much of the variance of the BDI-II items can be accounted for by a hierarchical higher order or a parallel dimension of depression, where much of the common variance can be explained by a general construct. Practitioners should be careful when interpreting subscale scores, which might be greatly related to the heterogeneous characteristics of depressive conditions.…”
Section: Content and Construct Validitymentioning
confidence: 67%
“…Concurrent validity was evaluated using -Khalek, 1998;Al-Musawi, 2001;Al-Turkait and Ohaeri, 2010) and the CES-D (Ghubash et al, 2000;Kazarian and Taher, 2010) were not selected because they have been validated in college students and community samples, not in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that the diagnostic reliability represents an upper limit on the psychometric performance of a screening test. Studies have also suggested the possibility that the instrument’s factors might actually measure specific depression symptoms of a more general, higher order depression factor [49, 50], which could be explored through use of bifactor or second-order factor model. Further research is needed to replicate and extend our findings in different patient groups and clinical settings.…”
Section: Discussionmentioning
confidence: 99%